The Use of Madrasah E-Learning for Online Learning during the Covid-19 Pandemic - Haris Firmansyah; Fandri Minandar (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to find out how to use Madrasah E-Learning in online learning during the Covid-19 pandemic by looking at three important aspects, including planning, implementation and evaluation. This study uses a qualitative research approach with descriptive methods. This type of qualitative research used is basic research. At the same time, the data collection techniques are through observation, interviews and documentation. Observations were made at Madrasah Aliyah Negeri 1 Pontianak. The results of this study are: (1) Madrasah e-learning will automatically store the planning data that the teacher compiles, and if it is needed to be printed, the teacher can print directly with the existing menu. (2) Implementation of learning during the COVID-19 pandemic, Madrasah e-learning is equipped with a video convergence menu, teachers and students can conduct virtual meetings. Students can also read the material provided in the teaching materials menu. And (3) Evaluation of E-learning Madrasah learning provides menus for conducting assessments. Cognitive assessment can be done in multiple-choice, essay, true-false, jump, which can be done in the Computer Based Test (CBT) menu.